Manager and consumer perspectives on fruit and vegetable availability and purchasing at Navajo Nation small stores - Piltch, Emily. (2018)
Abstract: The Navajo Nation (NN) is the largest federally recognized tribe in the U.S. More than half of Navajo residents live below the poverty line, 42% are unemployed, and one-third lack plumbing and electricity. In addition, the Navajo people have some of the highest rates of childhood obesity and food insecurity reported for a U.S. population. To reverse these public health challenges, the food environment must provide opportunities for healthy eating at affordable prices. The food environment challenges identified in urban, non-Native communities are structurally different from those faced in NN, so there is a specific need to develop approaches appropriate to local conditions. Convenience stores are the food outlets closest to 70% of Navajo communities, yet these small stores vary in their availability of healthy options. Little is known about the challenges and possible facilitators to supplying fruits and vegetables (F&V) to the most remote regions in NN. The research objectives addressed were to 1) determine F&V availability at all small stores in communities without grocery stores in NN, 2) document customer perspectives on barriers to and facilitators of purchasing F&V at these stores and, 3) understand store owner and manager views on stocking F&V. In Aim 1, we used a modified Nutrition Environment Measures Survey (NEMS) in stores to document all fresh, frozen and canned F&V at the 71 small stores in Navajo Nation communities without grocery stores. We also compared the fresh F&V offerings available at independently operated stores and regional and national chains. We found that nine stores had no fresh fruits and twelve stores had no fresh vegetables available. The overall median number of canned, fresh, and frozen F&V types offered across all stores were nine, eight and three, respectively. There were more fresh fruit and vegetable offerings at independently owned stores compared to regional or national chain stores (p < 0.05). Aim 2 explored perspectives on food availability and shopping preferences of 72 customers outside of 9 small stores in remote NN. Four individuals (5.6%) purchased some F&V at the small store the day s/he was interviewed and 32% had purchased some in the previous week. Most participants (64%) shopped primarily at super center stores outside of their communities, yet about half shopped at the small store at least twice per week. This suggests that the small stores are important spaces to encourage healthful food purchasing. Shoppers would be more inclined to purchase F&V if a greater variety were available at affordable prices. For Aim 3, interviews with six owners and 16 managers of 22 small stores in NN revealed that management would like to offer more fresh F&V. However, barriers exist, such as perceived low demand, limited F&V offerings from distributors and for some managers, minimal authority over product selection. Participants were interested in purchasing products from local farmers however few relationships exist and there was concern with food safety requirements. These findings document that increasing availability and purchasing of F&V in remote NN is complex and must address both supply and demand challenges. There are opportunities for increased dialogue among customers and management to encourage augmentation of product offerings. There is also need to explore creative sourcing, such as pooled purchasing among multiple locations, which could help stores increase variety while decreasing cost to customers. Given current product selection and varying levels of decision making autonomy, it will be necessary to pursue different strategies when looking to partner with independently owned stores compared to those that are part of regional or national chains. Study results will inform local programmatic and advocacy efforts to increase healthy food access in remote NN.; Thesis (Ph.D.)--Tufts University, 2018.; Submitted to the Dept. of Agriculture, Food and Environment.; Advisor: Tim Griffin.; Committee: Robert Houser, and Sonya Shin.; Keyword: Nutrition, and Public health.